Electro-chemo-mechanics of anodic porous alumina nano-honeycombs self-ordered growth and actuation - Cheng, Chuan; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2015)
In this thesis, real-time evolution of the nanopore channel growth and self-ordering process in anodic nanoporous alumina are simulated on the basis of an established kinetics model. The simulation results were in accordance with the experiments on the (i) growth sustainability of pore channels guided by pre-patterns; and (ii) substrate grain orientation dependence on self-ordering. In addition, a new fabrication method for the rapid synthesis of highly self-ordered nanoporous alumina is established, based on a systematic search for the self-ordering conditions in experiments. Lastly, it reports on a novel surface-charge induced strain in nanoporous alumina-aluminum foils, which indicates that nanoporous alumina can be used as a new type of actuating material in micro-actuator applications.
Research Background and Motivation -- Establishment of a Kinetics Model -- Numerical Simulation Based on the Established Kinetics Model -- Experimental Verification I: Growth Sustainability of Nanopore Channels Guided with Pre-Patterns -- Experimental Verification II: Substrate Grain Orientation Dependent Self-Ordering -- Quantitative Evaluation of Self-Ordering in Anodic Porous Alumina -- Fast Fabrication of Self-Ordered Anodic Porous Alumina on Oriented Aluminum Grains -- Charge-Induced Reversible Bending in Anodic Porous Alumina-Aluminum Composites -- Chemo-Mechanical Softening during In Situ Nanoindentation of Anodic Porous Alumina with Anodization Processing -- Conclusions and Future Work.
Electronic reproduction.
Keywords: Nanochemistry; Nanostructured materials; Self-assembly (Chemistry); Electronic books